2009
DOI: 10.1007/s10620-009-1046-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Impact of Capsule Endoscopy in Patients Referred for Iron-Deficiency Anemia

Abstract: Most patients referred for VCE examination to evaluate IDA were no longer anemic at 36 months of follow-up, with or without therapeutic intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 15 publications
1
29
1
Order By: Relevance
“…29 In the present study, VCE achieved a final diagnosis in 82.2% of patients; this proportion is higher than that observed in 2 recent reports that described a positive finding in 60% and 66%, respectively, of patients with IDA studied with VCE. 30,31 However, it should be underlined that the retrospective nature of both studies may explain the difference from our results. Nevertheless, the proportion of specific findings in the 2 studies was similar to ours, because arteriovenous malformation was largely the most frequent diagnosis (37% in both studies).…”
Section: Discussioncontrasting
confidence: 88%
“…29 In the present study, VCE achieved a final diagnosis in 82.2% of patients; this proportion is higher than that observed in 2 recent reports that described a positive finding in 60% and 66%, respectively, of patients with IDA studied with VCE. 30,31 However, it should be underlined that the retrospective nature of both studies may explain the difference from our results. Nevertheless, the proportion of specific findings in the 2 studies was similar to ours, because arteriovenous malformation was largely the most frequent diagnosis (37% in both studies).…”
Section: Discussioncontrasting
confidence: 88%
“…25 Seven of them were prospective 15,20,21,28,[33][34][35] and 17 were retrospective studies. [12][13][14][16][17][18][19][22][23][24][25][26][27][29][30][31][32] Only 2 were multicenter studies. 12,13 In all but 4 studies (in 3, not reported 18,23,27 and 1 study 31 with EndoCapsule [Olympus, Tokyo, Japan]), SBCE explorations were performed with capsule endoscopes from Given Imaging Ltd (Yoqneam, Israel).…”
Section: Descriptive Assessment and Study Characteristicsmentioning
confidence: 99%
“…Four publications focused exclusively on IDA patients (subset 1), 21,30,33,35 whereas in the remaining 20 articles, patients with IDA represented only a subgroup of a larger patient cohort undergoing SBCE (subset 2). [12][13][14][15][16][17][18][19][20][22][23][24][25][26][27][28][29]31,32,34 The QUADAS evaluation of the included studies is shown in Table 2. Nine QUADAS items (items 3-11) were not relevant and thus not assessed.…”
Section: Descriptive Assessment and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1 patient, CE missed an ulcer [23] . Sheibani et al [24] evaluated the long-term impact of CE in patients referred for iron deficiency anemia. CE had a diagnostic yield of 61% and the CE-based diagnosis led to a therapeutic intervention in about 26% of patients.…”
Section: Small Bowelmentioning
confidence: 99%